2020
DOI: 10.1158/1541-7786.mcr-19-1142
|View full text |Cite
|
Sign up to set email alerts
|

PTPN3 Inhibits the Growth and Metastasis of Clear Cell Renal Cell Carcinoma via Inhibition of PI3K/AKT Signaling

Abstract: The underlying molecular mechanism driving clear cell renal cell carcinoma (ccRCC) progression is still to be explored. The significant downregulation of protein tyrosine phosphatase non-receptor type 3 (PTPN3) expression in the tumor tissues suggested its protective role in ccRCC progression. Immunohistochemical analysis of PTPN3 protein in 172 ccRCC tissue revealed that PTPN3 was an independently favorable prognostic factor for progression-free survival (P = 0.0166) and overall survival (P = 0.0343) of patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The aberrant activation of the PI3K/Akt signaling pathway promotes the proliferation, migration and invasion of ccRCC cells ( 15 ). SPRR3 activates the PI3K/Akt pathway in colorectal and breast cancer cells ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aberrant activation of the PI3K/Akt signaling pathway promotes the proliferation, migration and invasion of ccRCC cells ( 15 ). SPRR3 activates the PI3K/Akt pathway in colorectal and breast cancer cells ( 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-338-3p inhibits the proliferation, migration and invasion of ccRCC cells (12)(13)(14); however, the underlying mechanism remains unclear, and to the best of our knowledge no study has reported the association between miR-338-3p and SPRR3. Activation of the PI3K/Akt signaling pathway promotes ccRCC progression (15). Furthermore, this pathway mediates the regulation of RCC cells by miR-338-3p (16).…”
Section: Introductionmentioning
confidence: 99%
“…35 In contrast, PI3K/AKT inhibition suppresses the metastasis and growth of ccRCC. 36 Therefore, we inferred that exosomal miR-15a from RCC cells accelerates cell viability by downregulating BTG2 and promoting PI3K/AKT signaling pathway activity.…”
Section: Discussionmentioning
confidence: 93%
“…Clear cell renal cell carcinoma, the predominant histologic subtype in RCC, has a high degree of malignancy. 1 , 2 However, molecular mechanisms underlying ccRCC tumorigenesis are still unclear, and new therapies targeting ccRCC are still challenging. 2 …”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 However, molecular mechanisms underlying ccRCC tumorigenesis are still unclear, and new therapies targeting ccRCC are still challenging. 2 …”
Section: Introductionmentioning
confidence: 99%